Proceedings of the International Conference "Economy in the Modern World" (ICEMW 2018) 2018
DOI: 10.2991/icemw-18.2018.13
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of methodical assessment tools of investment attractiveness of high-tech business as activator of innovation development

Abstract: The paper analyzes methodological approaches of the assessment of the investment attractiveness of a high-tech business in the current conditions of the development of the economic systems. The authors have taken up and shown the main problems of formation of the investment attractiveness of the hightech sector from the point of view of its impact on the quality of the investment development of the state economy, as well as on the building of innovative systems of various levels. The authors contributed to giv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…This chapter has also brought in sophistication in terms of studying the high-tech vs. non-hitech ventures as they differ in risk (hi-tech riskier), size of initial investment required (hi-tech higher), and the possibility of super-profits (hi-tech higher) (Doroshenko, Malykhina and Somina, 2018). Moreover, hi-tech ventures being closely linked to the scientific activities of education and research institutions (Antoniuk et al, 2017) may also benefit from the founder's general human capital (e.g.…”
Section: Duration Studies and The Panel Study Of Entrepreneurial Dyna...mentioning
confidence: 99%
See 1 more Smart Citation
“…This chapter has also brought in sophistication in terms of studying the high-tech vs. non-hitech ventures as they differ in risk (hi-tech riskier), size of initial investment required (hi-tech higher), and the possibility of super-profits (hi-tech higher) (Doroshenko, Malykhina and Somina, 2018). Moreover, hi-tech ventures being closely linked to the scientific activities of education and research institutions (Antoniuk et al, 2017) may also benefit from the founder's general human capital (e.g.…”
Section: Duration Studies and The Panel Study Of Entrepreneurial Dyna...mentioning
confidence: 99%
“…However, unlike non-tech start-ups, technology start-ups are characterised as a knowledge-intensive process, benefitting from higher educational attainment, and helping entrepreneurs to integrate varied market demands (Jianwen (Jon), Welsch and Moutray, 2009). High-tech businesses require a higher level of knowledge from entrepreneurs as access to diversified information helps them to allocate resources efficiently, which may lead them to product innovation (Marques et al, 2019), better planning and strategy adjustments leading to both time efficiencies (Doroshenko, Malykhina and Somina, 2018) and profitability. Research has shown that university (general) education is statistically significant to achieving hi-tech startups' investment milestones quicker benefitting from the founder's formal business and technical education (Ratzinger et al, 2018).…”
Section: Education and The Hi-tech Industrymentioning
confidence: 99%